HUBUNGAN ANTARA STRES KERJA DENGAN TINGKATDEPRESI PADA POLISI SABHARA POLRESTA BOGOR TAHUN 2019 - Tika Rahmawati (2020)
Depression is a mood disorder that causes distress and affects feeling, thought and daily activities. The prevalence of depression has increased significantly in a decade. One of the risk factors of depression is the presence of continuous pressure that may cause stress, which includes job stress. This study aims to determine the relationship between job stress with level of depression in Sabhara Police. This study was an observational analytic study using cross-sectional research design. The study was conducted at Polisi Resort Kota Bogor. The samples whom participated in this study were 68 respondents and purposive sampling techniques were used. The data was collected by using Job Stress Scale (JSS) and Patient Health Questionnaire-9 (PHQ-9) questionnaire. The result of this study showed that there were 39 Sabhara police (57.4%) with medium to high job stress and 32 Sabhara police (47.1%) had mild depression. Bivariate analysis by chi square showed that there was a relationship between job stress with level of depression in Sabhara Police (p = 0.000). The occupational stress experienced by the Sabhara police must be given special attention in order not to affect the occurrence of police depression. An understanding of appropriate coping mechanisms and stress management techniques needs to be given to the police